Sex differences in prehospital analgesia in patients presenting with acute coronary syndromes and their association with clinical outcomes. Issue 4 (23rd January 2022) - Nan Tie, Emilia; Fernando, Himawan; Nehme, Ziad; Dinh, Diem; Andrew, Emily; Brennan, Angela; Zaman, Sarah; Liew, Danny; Stephenson, Michael; Lefkovits, Jeffrey; Peter, Karlheinz; Duffy, Stephen J.; et al.
Abstract: Objectives: This study examined if sex differences in prehospital pain scores, opioid administration, and clinical outcomes exist in acute coronary syndrome (ACS) patients. Background: Sex differences persist in ACS presentation, management, and outcomes. The impact of sex differences on prehospital pain management of ACS with opioids is unknown. Methods: Patients presenting with ACS via ambulance (2014–2018) that underwent percutaneous coronary intervention (PCI) were prospectively collected via the Victorian Cardiac Outcomes Registry and Melbourne Interventional Group, linked to the Ambulance Victoria database. The primary outcome was 30‐day major adverse cardiac events (MACE). Secondary outcomes were descriptive analyses of prehospital pain score, intravenous morphine equivalent analgesic dosing, plus predictors of MACE and thrombolysis in myocardial infarction (TIMI) 0–1 flow pre‐PCI. Results: A total of 10, 547 patients were included (female: 2775 [26%]). Opioids were administered to 1585 (57%) females, 5068 (65%) males ( p  < 0.001). Adjusted 30‐day MACE was similar between opioid groups in both sexes (female: odds ratio [OR]: 1.21, confidence interval [CI] 0.82–1.79, p  = 0.34; male: OR: 0.89, CI: 0.68–1.16, p  = 0.40). Median pain score at presentation was 6 (interquartile range [IQR]: 4, 8) for both sexes. Median opioid dose was 2.5 mg (IQR: 0, 10) in females and 5 mg (IQR: 0, 10) in males ( p  < 0.001), with similar pain relief achieved. Adjusted rates of TIMI 0‐1 pre‐PCI were higher in patients administered opioids (female: OR 2.9, CI: 2.07–4.07, p  < 0.001; male: OR: 2.67, CI: 2.19–3.25, p  < 0.001). Conclusions: Female patients undergoing PCI received less opioid analgesia, but no sex differences in prehospital pain scores were seen. Opioid administration was associated with impaired antegrade flow in the culprit artery in both sexes, but not short‐term MACE. Trials evaluating nonopioid analgesics in ACS are needed.